Meningkatkan Kemampuan Sosial Anak TK Kelompok B Melalui Permainan Tradisional Kabadi-Kabadi - Tri Indah Rusli; Nur Cahaya; Nurul Idhayani; Wa Ode Sari Amalia; Yuliyanah Sain (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to improve children's social skills through implementing the Kabadi-kabadi Traditional game in Group B TK Ar-Rahman Tobengeano, North Kolaka Regency. The research uses a classroom action research (PTK) design with two cycles. The research subjects consisted of 16 children in Group B TK Ar-Rahman Tobengeano. Data is collected through observation and documentation of the learning process. The results showed that the implementation of the ball maze game significantly improved children's social abilities. In cycle I, there was an increase from 40% to 72.22%, and in cycle II the success rate was 93.75%. The implication of this research is that the ball maze game can be used as an effective alternative method in developing the social skills of children aged 5-6 years. It is expect that this research can contribute to the development of learning strategies in kindergarten and provide guidance for teachers to design learning activities that support children's social development.